STUDY ON THE BIOACCUMULATION OF HEAVY METALS IN COMMERCIALLY VALUABLE AND EDIBLE MARINE SPECIES OF ENNORE CREEK, SOUTH INDIA - P. CHITRARASU; A. JAWAHAR ALI; T. BABUTHANGADURAI (International Journal of Pharma and Bio Sciences, 2013)
A systemic study has been undertaken to establish a baseline data on the profiles of on the heavy metals (Cu, Cr, Zn, Ni, Pb and Cd) in the biota of Ennore Creek environment. Samples of fishes (Oreochromis mossambica, Mugil cephalus, Clarias batrachus and Channos channos), shrimps (Penaeus monodon and Penaeus indicus), crab (Portunus pelagicus) and mussels (Perna viridis, Mytilus gravincia provincialis and Crassostrea madrasensis) have been subjected to analyses. These selected biota have highly commercial value and are edible. The concentrations of Pb and Cd in the mussels (6.4 ± 0.52 mg.kg-1and 3.9 ± 0.40 mg.kg-1 respectively) exceeding the permissible limits recommended by FAO, USFDA and European Commission for food standards. The concentration of heavy metals (Cu (11.1 to 19.0 ), Ni (0.9 to 6.35), Cr (1.43 to 3.56), Cd (0 to 2.4), Pb (0.7 to 3.7) and Zn (4.6 to 24.0) mg.kg-1) in the fish and crustaceans (Cu (15.9to 21.1), Ni (5.7 to 8.8), Cr (1.9 to 2.3), Cd (1.7 to 2.5), Pb (2.0 to 2.8) and Zn (47.8 to 56.7) mg.kg-1) species also moderately higher and slightly exceeding the permissible limits. The bivalve mollusc, Crassostrea madrasensis have been identified to accumulate higher concentrations of non-essential (Cu (22.3 to 26.3), Ni (7.36 to 10.4), Cr (2.73 to 4.63), Cd (2.3 to 3.90) and Pb (5.2 to 6.40) mg.kg-1) and essential (Zn (90.1 to 157) mg.kg-1) heavy metals suggesting that they could serve as bioindicator of severe heavy metal pollution in the Ennore Creek environment.